ANALISIS NILAI PATRIOTISME NOVEL 693 KM JEJAK GERILYA SUDIRMAN KARYA AYI JUFRIDAR - Nurjannah Nurjannah; Radhiah Radhiah; Trisfayani Trisfayani (Program Studi Pendidikan Bahasa Indonesia, STKIP Bina Bangsa Getsempena, 2021)
This research aims to describe the value of patriotism in the novel 693 KM Jejak Gerilya Sudirman by Ayi Jufridar. This research is qualitative descriptive. The data in this research are sentences containing the value of patriotism in the novel 693 Km Jejak Gerilya Sudirman by Ayi Jufridar. The data source is the novel 693 KM Jejak Gerilya Sudirman by Ayi Jufridar. Data collection techniques used literature review and reading-note techniques. The data analysis technique in this study uses flow analysis technique which include three components, such as data reduction, data presentation, and conclusion. The results showed that there was a value of patriotism in the novel 693 KM Jejak Gerilya Sudirman by Ayi Jufridar. The value of patriotism for loving the homeland is 8 data, willing to sacrifice is 23 data, emphasizes unity, integrity and safety of the nation above personal interest is 7 data, patriotism with a reformer spirit is 10 data, and never giving up is 22 data. The most value of patriotism in the novel 693 Km Jejak Gerilya Sudirman by Ayi Jufridar is willing to sacrifice totaling 23 data. The least value of patriotism is emphasizes unity, integrity and safety of the nation, which also amounts to 7 data in the novel 693 Km Jejak Gerilya Sudirman by Ayi Jufridar. Abstrak Penelitian ini bertujuan untuk mendeskripsikan nilai patriotisme novel 693 KM Jejak Gerilya Sudirman karya Ayi Jufridar. Jenis penelitian yang digunakan yaitu deskriptif kualitatif. Data dalam penelitian ini ialah kalimat-kalimat yang mengandung nilai patriotisme dalam novel 693 Km Jejak Gerilya Sudirman karya Ayi Jufridar. Sedangkan sumber datanya ialah novel 693 KM Jejak Gerilya Sudirman karya Ayi Jufridar. Teknik pengumpulan data yang digunakan yaitu teknik kepustakaan dan teknik baca-catat. Teknik analisis data dalam penelitian ini menggunakan teknik analisis mengalir yang meliputi tiga komponen yaitu reduksi data, penyajian data, dan penarikan simpulan. Hasil penelitian menunjukkan bahwa terdapat nilai patriotisme dalam novel 693 KM Jejak Gerilya Sudirman karya Ayi Jufridar. Nilai patriotisme cinta tanah air berjumlah 8 data, rela berkorban 23 data, mementingkan persatuan dan kesatuan serta keselamatan bangsa di atas kepentingan pribadi berjumlah 7 data, nilai patriotisme berjiwa pembaharu 10 data, serta nilai pantang menyerah berjumlah 22 data. Nilai patriotisme yang dominan dalam novel 693 Km Jejak Gerilya Sudirman karya Ayi Jufridar adalah nilai patriotisme rela berkorban berjumlah 23 data. Sedangkan nilai patriotisme yang minim adalah nilai patriotisme mementingkan persatuan dan kesatuan serta keselamatan bangsa juga berjumlah 7 data dalam novel 693 Km Jejak Gerilya Sudirman karya Ayi Jufridar. Kata Kunci: Analisis, Nilai, Patriotisme, Nilai Patriotisme, Novel